Case Report: Rheumatoid meningitis with positive NMDAR antibody: A case treated with intravenous immunoglobulin - Zhang, Honglian; Wan, Yuehong; Mei, Zhujun; Xie, Chen; Liu, Shiying; Nie, Hongbing; Hu, Fan; Xu, Renshi (Frontiers in Immunology, 2022)
As a rare complication of rheumatoid arthritis (RA) in the central nervous system (CNS), rheumatoid meningitis (RM) mainly affects the meninges and has various clinical symptoms. The diagnostic and treatment approaches currently used are not practical. RM cases with positive NMDAR antibodies (Abs) have never been reported. In the present study, a 66-year-old man with a 1-year history of RA presented recurrent left lower limb weakness during activities for 1 month. The results showed that rheumatoid factor (RF) and anti-cyclic citrullinated peptide antibody (ACPA) were positive in the serum, and NMDAR Abs were present in cerebrospinal fluid (CSF). Hyperintensity was observed in the leptomeninges of the right frontal and parietal lobes, and subtle hyperintensity was observed in the left frontal and parietal lobes, as indicated by brain MRI. A meningeal biopsy revealed non-specific inflammation with the absence of rheumatoid nodules. The patient was given IVIg on day 7 after admission. The clinical symptoms were relieved, the lesions were alleviated, and abnormal biochemical indicators were gradually recovered 1 week after initiation of the treatment, while NMDAR Abs were present in CSF even after treatment. After 5 months of follow-up, the patient’s serum and CSF ACPA and IL-6 levels were still high. The findings showed that brain MRI was adequate for the diagnosis of RM. ACPA and IL-6 might be the specific biomarkers for disease activity in RM. IVIg was effective as induction therapy for RM. Further studies should explore whether the presence of NMDAR Abs is associated with RM.